Laparoscopic entry traditional methods, new insights and novel approaches (Springer London, 2012)
Laparoscopic Entry: Traditional Methods, New Insights And Novel Approaches discusses traditional methods of laparoscopic surgery, new devices, laparoscopic entry in difficult patients, robotic assisted surgery access, single port entry, gasless access, transvaginal entry and natural orifice surgery. This book illustrates, through the presentation of techniques, methods, photos, images, drawings and pictures, all the possible methods of laparoscopic entry for endoscopic surgeons, either for laparoscopy or for robotics. Laparoscopic Entry: Traditional Methods, New Insights And Novel Approaches describes problems and criticisms of each method and highlights common and rare complications. Written by experts in the field, this book also includes tips and tricks, which can be tailored to each patient, making it a valuable reference tool for gynecologists, urologists, vascular and general surgeons.